Segunda pessoa e casos-limite em Paul Ricoeur - Tiellet, Claudia Aita (2020)
The present research starts from the observation of the philosopher Paul Ricoeur, who, like two major philosophical ethical traditions, a chain of teleology in the wake of Aristotle and a chain of deontology in Emmanuel Kant, treats the second person of ethics in an obliterated way. The chain of teleological ethics sees civic virtue or humanity only in friendship (philia) between men, free and equal. Interpersonal relationships are only possible or reasonable if those involved are predominantly male, from the same and higher socioeconomic class. The current of deontological morality, in turn, brings with it the modern ideal of an autonomous subject that constantly clashes with the demand for reciprocity in interpersonal relationships. Both traditions, therefore, do not overcome the initial dissymmetry, based on the theories of deposition of the other and cultivate inertia in the face of so much violence. Thinking about the suffering of the second person immersed in these situations of inequality, the French philosopher points out a way out, arising from the articulation and complementarity between ethics, from the notion of solicitude, and moral, from the category of respect. Thus, we will defend that Ricoeur corrects the deficiencies in the treatment of the second person of ethics, in accordance with the premises of solicitude and respect and the search for articulation between ethics and morals. Our proposal will be better understood from the analysis of the way in which our philosopher operates deliberation, or moral judgment in a singular situation, through the examination of limit cases.